2021
DOI: 10.4081/ija.2021.1870
|View full text |Cite
|
Sign up to set email alerts
|

Discovering genetic diversity of Changmaogu, a rice landrace, for conservation and rural development

Abstract: Changmaogu is a very rare and endangered rice landrace cultivated in a very limited area by Lama people, a branch of Bai ethnic group in Lanping County, Yunnan, China. No study on this precious landrace had been reported. This study was intended to explore the genetic diversity so as to develop strategy for conserving Changmaogu. The Changmaogu samples were compared with other three varieties (Hejing 16, Nipponbare and Hongxiangmi), using 24 pairs of SSR markers. Among all varieties, Changmaogu showed the rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Like other attributes, chilling stress tolerance of rice is most likely regulated by various genes depending on phenological stages ( Cruz et al, 2013 ; Zhang et al, 2017 ) as well as the rice landraces. Recently He et al (2021) , reported about genetic diversity of rice landraces triggering a high degree of non-degradation adaptability to the local environment of China. According to the report, the diversity of natural and farmer choice in the course of agricultural events advances to very balanced agronomic characteristics within the population of landrace, ( Pusadee et al, 2009 ; Song et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like other attributes, chilling stress tolerance of rice is most likely regulated by various genes depending on phenological stages ( Cruz et al, 2013 ; Zhang et al, 2017 ) as well as the rice landraces. Recently He et al (2021) , reported about genetic diversity of rice landraces triggering a high degree of non-degradation adaptability to the local environment of China. According to the report, the diversity of natural and farmer choice in the course of agricultural events advances to very balanced agronomic characteristics within the population of landrace, ( Pusadee et al, 2009 ; Song et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently He et al (2021), reported about genetic diversity of rice landraces triggering a high degree of non-degradation adaptability to the local environment of China. According to the report, the diversity of natural and farmer choice in the course of agricultural events advances to very balanced agronomic characteristics within the population of landrace, (Pusadee et al, 2009;Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%